Labor demand during the crisis: What happened in Germany? - Olga Bohachova; Bernhard Boockmann; Claudia M. Buch (Center for Economic Studies and ifo Institute (CESifo), 2011)
In Germany, the employment response to the post-2007 crisis has been muted compared to other industrialized countries. Despite a large drop in output, employment has hardly changed. In this paper, we analyze the determinants of German firms' labor demand during the crisis using a firm-level panel dataset. Our analysis proceeds in two steps. First, we estimate a dynamic labor demand function for the years 2000-2009 accounting for the degree of working time flexibility and the presence of works councils. Second, on the basis of these estimates, we use the difference between predicted and actual employment as a measure of labor hoarding as the dependent variable in a cross-sectional regression for 2009. Apart from total labor hoarding, we also look at the determinants of subsidized labor hoarding through short-time work. The structural characteristics of firms using these channels of adjustment differ. Product market competition has a negative impact on total labor hoarding but a positive effect on the use of short-time work. Firm covered by collective agreements hoard less labor overall; firms without financial frictions use short-time work less intensively.
Keywords: J23; J68; G32; 330; labor demand; economic crisis; short-time work; financial frictions; labor market institutions; employment adjustment